Screening Test for Infection in Childern with SLE by C – reactive Protein Level - Wisanuytin, Suwannee; Thungkanopas, Araya; Kirdpon, Sukachart; Jiravuttipong, Apichat (Srinagarind Medical Journal, 2013)
Background : Infections are common in children with systemic lupus erythematosus (SLE) due to the disease itself and/or the treatment of SLE with immunosup – pressants. Notwithstanding. These infections may be difficult to differentiate from reactivation of SLE C – reactive protein (C-RP) is a rapid and direct indicator for acute phase reaction. Therefore, C – RP may be useful for early detection of and infections condition in children with SLE. Objective : To detect the cut – off point of a c – RP level for early detection of an infectious condition among SLE patients and to evaluate the sensitivity, specificity, positive and negative predictive values for the selected C – RP Design : Prospective study (diagnostic test) Setting : Srinagarind Hospital Measurements : C – RP levels in SLE patients with and infectius condition and those with a non – infectious condition. Results : 228 samples of serum from 33 patients with SLE were tested for the C-RP level by turbidimenter during March 1,2000 and February 28, 2001. Intercurrent infection were documented in 41 episodes (17.9%) of those patients. At a C – RP level > 6 mg/I, the sensittvity and specificity to detect an infection was 100 and 94 percent, respectively. The positive and negative predictive values were 79 and 100 percent, respectively. Conclusion : The C – RP level is a rapid and accurate method of detecting intercurrent infections in children with SLE patients.